Perceived attachment security to parents and peer victimization: Does adolescent's aggressive behaviour make a difference?. (6th April 2018) - Guedes, Maryse; Santos, António J.; Ribeiro, Olívia; Freitas, Miguel; Rubin, Kenneth H.; Veríssimo, Manuela
ABSTRACT: Peer victimization is one of the most prominent problems during adolescence. Research has distinguished aggressive and non‐aggressive victims; however, there are still significant drawbacks in understanding the social and family functioning of these different groups of victimized adolescents. This study aimed to compare social behavior and perceived attachment security to parents of Portuguese adolescents, classified as aggressive victims, non‐aggressive victims and non‐victims. The sample consisted of 222 adolescents (115 boys, 107 girls) who completed the Kerns Security Scale and the Extended Class Play, to assess perceived attachment security and social behavior, respectively. Controlling for age and sex, aggressive victims and non‐aggressive victims differed in anxious withdrawal but shared a similar profile in peer exclusion and prosocial behavior. Only aggressive victims reported lower attachment security to mother and father when compared to non‐victims. These findings underline that victimized adolescents constitute a heterogeneous group in terms of their social and family functioning.